The Employment Relationship in Australia - Dabscheck, Braham (Relations industrielles / Industrial Relations, 1996)
The Employment Relationship in Australia by Tom Keenoy and Di Kelly is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z